Hybrid Governance and Social Capital in Kemiren Village Tourism Development and Resilience - Dani Aditya Gunawan; Nabil Lintang Pamungkas (Journal of Transformative Governance and Social Justice, 2026)
Indigenous tourism villages currently face a dilemma between local economic growth and the potential for excessive cultural commodification. Kemiren Village represents a unique sociological resilience anomaly amidst the dynamics of the modern economy, but still maintains the existence of their Osing culture. This study aims to analyze the role of social capital in Kemiren Village, specifically focusing on how each actor mobilizes embedded resources to build a hybrid governance system amidst the expansion of tourism in modern era. This qualitative descriptive-analytical study uses a social constructivism paradigm by examining the social capital of each actor. Data were collected through participant observation, archival documentation, and semi-structured interviews with 6 key informants during the field research period in June 2026. The findings were systematically analyzed based on the framework of Nan Lin's Social Capital and W. Richard Scott's New Institutionalism. The concept of Nan Lin Social Capital in Kemiren Traditional Village does not operate as an egalitarian communal bond, but rather embodies embedded resources through a Hybrid Governance structure, integration of formal state tourism administration with indigenous normative laws. The network's location in villages provides systematic differential access and marginalizes marginalized actors. Interview data revealed that elite groups, such as BUMDes and Pokdarwis, monopolize and control the flow of tourist guests, while the confessions of MSME actors in the outlying areas (Kemiren Etan) confirmed that they were alienated from access to the tourist market. To mitigate this conflict of inequality, village actors implemented Hybrid Governance, a hybrid of modern bureaucracy, adherence to village regulations, and customary sanctions. This approach was validated by informants' testimony regarding the collective fear of Buyut Cili's ancestral curse, which proved effective in disciplining residents and tourists from consuming the Tumpeng Sewu dish before the sacred prayer at the mosque was completed. Despite this and amidst the pressures of mass commodification and cultural festivalization, the resilience of the Osing tribe's civilization remains strong through adaptive resistance strategies, successfully defending against the monopoly of global market capital flows. This study extends Nan Lin's theory and modifies Scott's Institutionalism by proving that social capital inequality actually underlies the birth of hybrid institutions that protect tradition. They pragmatically tolerate bureaucratic imbalances while using hybrid governance as an institutional safety net to strictly protect their sacred ancestral philosophy.